Compressive Sensing and its Application to Speech Signal Processing - Dr. Mahesh T. Kolte, Pooja C. Nahar, (International Journal of Scientific Research and Management (IJSRM), 2017)
Compressed sensing or compressive sensing or Compressive sampling or CS is a revolutionary technique that strongly relies on sparsity of signal. CS has been applied in areas like Radar systems, sonar systems, video signal, and image processing etc. This paper will discuss the potential implementation of CS technology on speech signal and the compression rate that can be achieved.